Carbon emission reduction in China’s iron and steel industry through technological innovation: a quadrilateral evolutionary game analysis under government subsidies - Xinfa, Tang; Shuai, Liu; Yonghua, Wang; Youwei, Wan; Dirane Nubea, Musa (Frontiers in Environmental Science, 2025)
The steel industry is notable for its significant environmental impact, highlighting the pressing need to promote technological innovation within the sector in order to reduce carbon emissions. This paper utilizes a quadrilateral evolutionary game model to analyze the strategic behaviors of steel producers, construction companies, scrap steel recyclers, and the government throughout the entire steel production, consumption, and recycling processes and their impact on carbon emission reduction. The analysis and simulation of the model provide policy insights for these four key players. The study’s findings are as follows: (i) Government subsidies can effectively stimulate low-carbon production methods and encourage green consumer behavior. (ii) The strategic choices for technological innovation by steel manufacturers and scrap steel recyclers are primarily influenced by cost factors. Government subsidies for technological innovation play a crucial role in incentivizing a smooth transition to low-carbon production methods. (iii) For steel manufacturers, the carbon benefits derived from technological innovation are a critical factor influencing their engagement in such initiatives. If these manufacturers can benefit from environmental regulations, they are more likely to engage in technological innovation. (iv) The strategies of construction companies are influenced by production costs and carbon benefits associated with steel manufacturers, exhibiting threshold effects.